2019
DOI: 10.1080/1461670x.2019.1633243
|View full text |Cite
|
Sign up to set email alerts
|

Refugee and Asylum News Coverage in UK Print and Online Media

Abstract: The representation of asylum is important, yet there is little research of how this topic is reported online. This article addresses this gap through a study of UK print and online media (N = 2018). Articles were examined for their soft and hard news focus. Results show both partisanship and the medium play an important role. Online news covered more soft and hard news topics regardless of partisanship. However, examining the focus and style, right-leaning print and online publications focused more on criminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…Por sua vez, o estudo de Blumell et al (2020), com base na cobertura de média online do Reino Unido, mostra que há uma sobrevalorização da criminalidade cometida pelos requerentes de asilo e uma politização deste tema: os média considerados de esquerda focam-se na vitimização, enquanto os de direita, na criminalidade. Os autores apontam a necessidade de mais soft news sobre refugiados, e não apenas hard news, para dar mais contexto, personalização e esclarecimento ao tema.…”
Section: Quem é O Refugiado Nos Média?unclassified
“…Por sua vez, o estudo de Blumell et al (2020), com base na cobertura de média online do Reino Unido, mostra que há uma sobrevalorização da criminalidade cometida pelos requerentes de asilo e uma politização deste tema: os média considerados de esquerda focam-se na vitimização, enquanto os de direita, na criminalidade. Os autores apontam a necessidade de mais soft news sobre refugiados, e não apenas hard news, para dar mais contexto, personalização e esclarecimento ao tema.…”
Section: Quem é O Refugiado Nos Média?unclassified
“…• They are part of students' daily lives, engaging and provoking emotional responses; • If "fake news" mimic journalistic practices and "look like news," the strategies to mimic those practices can be analysed and deconstructed; • Students are exposed to racist and hateful discourses and are manipulated by the use of their preferred media outlets: Research has shown that online media tends to portray immigrants, refugees, and asylum seekers more often as threats than print media does (Blumell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As De Lemos and colleagues suggest [ 7 ], such a political debate is mediated by mass media, who play a fundamental role in the social representation of refugees. Studies in this field show that, while right wing media focus their narratives on crime and legality, left wing parties focus on refugee victimization [ 8 ]. Nowadays, the term “refugee” has assumed an emotional meaning in addition to the original institutional meaning that had the specific function of ensuring secure shelter for those displaced because of persecution, conflict, violence, and human rights violations.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the term “refugee” has assumed an emotional meaning in addition to the original institutional meaning that had the specific function of ensuring secure shelter for those displaced because of persecution, conflict, violence, and human rights violations. According to the narratives shared by the mass media in western countries, refugees are either people to fear or to rescue [ 8 ]. Although qualitatively different, these representations foster an image of refugees as resourceless foreigners who merely consume the host community’s resources produced by natives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation